Seasonal and temporal trends in childhood conjunctivitis in Burkina Faso - Sié, Ali; Bärnighausen, Till (The American journal of tropical medicine and hygiene, 2018)
Acute conjunctivitis follows a seasonal pattern. Although its clinical course is typically self-limited, conjunctivitis epidemics incur a substantial economic burden because of missed school and work days. This study investigated seasonal and temporal trends of childhood conjunctivitis in the entire country of Burkina Faso from 2013 to 2016, using routine monthly surveillance from 2,444 government health facilities. A total of 783,314 cases were reported over the 4-year period. Conjunctivitis followed a seasonal pattern throughout the country, with a peak in April. A nationwide conjunctivitis outbreak with a peak in September 2016 was noted (P < 0.001), with an excess number of cases first detected in June 2016. Nationwide passive surveillance was able to detect an epidemic 3 months before its peak, which may aide in allocation of resources for containment and mitigation of transmission in future outbreaks.
Gesehen am 24.09.2019